Civility and the Other: Three American Women Writers Address Oppression - Durham, Kathleen (My University, 2020)
The ubiquitous, polite side of civility connotes good manners, respect, and consideration. The violent side of civility, however, defines itself in terms of codes , or rules, used by the civilized to control uncivilized Others they intend to exploit or replace face developed over centuries. These women authors present perspectives that integrate alternative experiences of the evolved codes of civility that in part enabled Amere. In this thesis, I analyze three short stories by American women authors who reveal the oppressive side of civility and who makes the rules that unjustly govern particular societies. The selected stories are : “The Lullaby” by Leslie Marmon Silko, “A Girl’s Story” by Toni Cade Bambara, and “The Displaced Person” by Flannery O'Connor. The ethnicities the authors create are a multicultural platform to review unjust codes of civility dividing citizens within their communities and in the nation. These narratives—local in setting yet universal in their messages—convincingly portray how the meaning of and practice of civility can contradict one another in devastating ways. Likewise, the synthesis of this multicultural analysis comprehends an instructive binary opposition between civility and codes of civility. Studying how codes addressed in these stories negate civility reveals the corrupting side of civility, the side that must be exposed to understand the societal cancer it causes. Such study can result in self-examination, which can then lead to individuals’ changes in societal behaviors and reduce Othering and marginalization of people and communities. All the stories take place in the twentieth century, yet the particular forms of Othering the characters face developed over centuries. These women authors present perspectives that integrate alternative experiences of the evolved codes of civility that in part enabled America to achieve its predominance in the world.
Chapter I: INTRODUCTION 1 -- Incivilities in Today’s Fiction Rooted in Past Oppressions 1 -- Chapter II: LOSS AND FORGIVENESS IN “LULLABY” 24 -- Chapter III: PRAGMATISM TEACHES SELF-RELIANCE 46 -- Chapter IV: CODES OF CIVILITY CORRUPT THE FARM 60 -- Chapter V: CONCLUSION 83 -- The Price of Oppression 83 -- BIBLIOGRAPHY 90
Keywords: Academic theses; Bambara, Toni Cade; O'Connor, Flannery; Racism; Silko, Leslie Marmon, 1948-; Women in literature; Women's rights; Women